Complement-independent retinal pathology produced by intravitreal injection of neuromyelitis optica immunoglobulin G. Issue 1 (December 2016) - Felix, Christian; Levin, Marc; Verkman, Alan
Abstract Background Neuromyelitis optica (NMO), an autoimmune inflammatory disease of the central nervous system, is often associated with retinal abnormalities including thinning of the retinal nerve fiber layer and microcystic changes. Here, we demonstrate that passive transfer of an anti-aquaporin-4 autoantibody (AQP4-IgG) produces primary retinal pathology. Methods AQP4-IgG was delivered to adult rat retinas by intravitreal injection. Rat retinas and retinal explant cultures were assessed by immunofluorescence. Results Immunofluorescence showed AQP4-IgG deposition on retinal Müller cells, with greatly reduced AQP4 expression and increased glial fibrillary acidic protein by 5 days. There was mild retinal inflammation with microglial activation but little leukocyte infiltration and loss of retinal ganglion cells by 30 days with thinning of the ganglion cell complex. Interestingly, the loss of AQP4 was complement independent as seen in cobra venom factor-treated rats and in normal rats administered a mutated AQP4-IgG lacking complement effector function. Exposure of ex vivo retinal cultures to AQP4-IgG produced a marked reduction in AQP4 expression by 24 h, which was largely prevented by inhibitors of endocytosis or lysosomal acidification. Conclusions Passive transfer of AQP4-IgG results in primary, complement-independent retinal pathology, which might contribute to retinal abnormalities seen in NMO patients.